Balanced Scorecard and Strategy Map Design in The Company (Case Study at PT. Astra Agro Lestari) - Ivan Godang Wardiman; Syukri Lukman (PT Mattawang Mediatama Solution, 2023)
This study aims to analyze the performance of PT Astra Agro Lestari using the balanced scorecard and strategy map. Researchers use secondary data through the company's annual report and literature review. The results obtained, starting from a growth and learning perspective, have three strategic objectives and KPIs. Then the internal business process perspective has 5 strategic goals and KPIs. From the customer perspective, it has 3 strategic goals and KPIs. From a financial perspective, it also has 3 strategic goals and KPIs. Furthermore, each prepared strategy is visualized through a strategy map.